Highly Specific and Sensitive Detection of Yersinia pestis by Portable Cas12a-UPTLFA Platform - You, Yang; Zhang, Pingping; Wu, Gengshan; Tan, Yafang; Zhao, Yong; Cao, Shiyang; Song, Yajun; Yang, Ruifu; Du, Zongmin (Frontiers in Microbiology, 2021)
Recent discovery of collateral cleavage activity of class-II CRISPR-Cas (Clustered regularly interspaced short palindromic repeats-CRISPR associated protein) effector proteins make CRISPR-based diagnosis a potential high-accuracy nucleic acid detection method. Colloidal gold-based lateral flow immunochromatographic assay (LFA), which has been combined with CRISPR/Cas-based nucleic detection, usually associates with drawbacks of relative high background and the subjectivity in naked-eye readout of the results. Here, we developed a novel system composed of Cas12a-based nucleic acid detection and up-converting phosphor technology (UPT) based LFA (UPT-LFA), termed Cas12a-UPTLFA. We further demonstrated the utility of this platform in highly sensitive and specific detection of Y. pestis, the causative agent of deadly Plague. Due to high infectivity and mortality, as well as the potential to be misused as bioterrorism agent, an culture-free, ultra-sensitive, specific and rapid detection method for Y. pestis has long been desired. By incorporating isothermal recombinase polymerase amplification (RPA), the Cas12a-UPTLFA we established can successfully detect genomic DNA of Y. pestis as low as 3 attomolar (aM), and exhibited high sensitivity (93.75%) and specificity (90.63%) for detection of spiked blood samples with a detection limit of 102 colony forming unit (CFU) per 100 μL mouse blood. With a portable biosensor, Cas12a-UPTLFA assay can be operated easily by the non-professional personnel. Taken together, we have developed a novel Cas12a-UPTLFA platform for rapid detection of Y. pestis with high sensitivity and specificity, which is portable, not expensive and easy to operate as a point of care method. This detection system can easily be extended to detection of other pathogens and holds great promise for on-site detection of emerging infectious pathogens.